Assistance in the Use of a Website-Based Disability Sports Competition Management System for NPCI Coaches and Officials throughout East Java - Dwi Cahyo Kartiko; Irmantara Subagio; Bayu Budi Prakoso; Suryanto Agung Prabowo; Rudi Rudi; Roy Agustinus Soselisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
National Paralympic Committee Indonesia (NPCI) East Java manages disability sports competitions across East Java Province. However, competition management faces three major challenges: (1) the absence of technology-based competition management systems; (2) limited understanding of disability classification among coaches and officials leading to frequent misplacement of athletes; and (3) infrequent competency enhancement activities for district/city NPCI coaches and officials. This community service (PkM) activity aimed to accompany coaches and officials from NPCI across East Java in using a website-based competition management system, implemented directly during the East Java Provincial Paralympic Championship (Peparprov II) 2024, June 13–17, 2024, at the Oentoeng Poedjadi Athletics Track, FIKK Universitas Negeri Surabaya. A total of 92 coaches and officials from 29 districts/cities participated actively. Evaluation of training quality using a 19-item instrument across four aspects showed an overall average of 4.49 (89.9%), categorized as very good, with presenter competence receiving the highest score (4.51; 90.3%). Website usability evaluation using 19 items across four dimensions showed an overall average of 4.12 (82.5%), categorized as good, with ease of use and content dimensions receiving the highest scores (4.15; 83.0%). Outcomes achieved include improved competencies of coaches and officials, successful implementation of the website system during Peparprov II, mass media publication, and a formal cooperation agreement between FIKK Unesa and NPCI East Java.